Voting When the Stakes Are High - Jørgen Juel Andersen; Jon H. Fiva; Gisle James Natvik (Norges Bank, 2010)
Rational choice theories of electoral participation stress that an individual's decision to vote depends on her expected net benefit from doing so. If this instrumental motive is relevant, then turnout should be higher in elections where more is at stake. We test this prediction, by studying how turnout is affected by exogenous variation in governments' financial flexibility to provide pork for their voters. By utilizing simultaneous elections for different offices, we identify a positive effect of election stakes on turnout.
hdl:11250/2497448
Keywords: D72; H71; 330; voter motivation; elections; turnout